Relationship of financial literacy and financial inclusion in increasing the performance of angkringan SME in Bekasi - Purwanti; Elsye Fatmawati (Enrichment : Journal of Management, 2023)
The background of this research is that financial literacy and inclusion affect SME performance. Many SMEs experience obstacles in their growth due to the lack of knowledge about entrepreneurship and the ability to access financial services to obtain business capital. This quantitative study uses 60 respondents. This study collected data using a literature review, observations, and questionnaires to Bekasi angkringan SMEs. The research uses multiple linear regression analysis and hypothesis testing. This study found that financial literacy and inclusion improve the performance of angkringan SMEs in Bekasi.